English as a Foreign Language Learners’ Perceptions of Critical Thinking in Academic Writing: A Case of Vietnamese University Students - Luu Thi Mai Vy (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This study investigates Vietnamese university learners’ perceptions of integrating critical thinking (CT) into second language (L2) acquisition, with a particular focus on its application in academic writing (AW). The primary objectives are to explore how these learners conceptualize CT in AW, assess their self-evaluation of CT application in their academic writing, identify the challenges they face, and determine the resources needed to enhance CT in this context. The study sample consisted of 91 English-major undergraduates, selected through purposive and convenience sampling, who had recently completed a research methodology course at a private university in Vietnam. A questionnaire was administered to all 91 participants, followed by in-depth interviews with 11 students to gain further insights. Quantitative data were analyzed using SPSS 23, while qualitative responses underwent thematic analysis. The findings indicate that students demonstrated a sound understanding of the role of CT in AW and reported a moderate level of confidence in their CT abilities. However, they also acknowledged specific challenges, such as difficulties navigating the overwhelming amount of information and a lack of explicit instruction and guidance in developing CT for AW. These findings suggest important pedagogical implications for supporting English as a Foreign Language (EFL) learners in Vietnam in cultivating CT within academic writing. Received 15th December 2024; Revised 5th March 2025; Accepted 12th April 2025